Tool wear and chipping modelling for micro machining - Lim, Jia Yaw. (2011)
The use of Taguchi method via analysis of variance (ANOVA) was used in this report to find out more about the relationship between the four parameters and the cutting tool. The four parameters are cutter feed of cutting tool, depth of cut of cutting tool, rake angle of cutting tool and the spindle speed of the machine. The optimal control factor level was found out and Ansys stimulation was done to evaluate the mechanism of micro machinery tools. The result from Ansys helps to predict the breakage of cutting tool and the value of Von mises stresses of the cutting tool was analyse to give similar result with the analysis of variance method. Larger tool wear and chipping was found to occur more with a larger cutting forces. The most significant factors to the least significant factors for resulting in a bigger cutting force experienced by the cutting tool is the rake angle with a percentage of 40.8 followed by the depth of cut with a percentage of 31.5 and the spindle speed and cutter feed with a 10.4 percent and 5.9 percent accordingly.